DANCE AND MOVEMENT THERAPY: A MIXED-METHODS SYSTEMATIC REVIEW - Zande, Marta; Šuriņa, Sanita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Changes caused by aging manifest themselves in physical, cognitive, emotional and social areas. Dance and movement therapy ensures that it is possible to work with a client in all four areas – promote physical activity, stimulate cognitive functions, activate emotional component and encourage social interactions. The aim of this research was to create a mixed methods systematic review on dance and movement therapy (DMT) for seniors, to assess the methodological quality of included studies, analyse structural and content indicators of applied DMT interventions, their effect and experience of seniors gained during dance and movement therapy sessions. Findings suggest that the methodological quality of studies varies from high to low. Data acquired by meta-analysis indicates a statistically significant reduction of depression scores for research (DMT) group in comparison to control group (95% CI: -3.74 to -2.52, total effect Z = 10.05 (P < 0.00001)). Qualitative data shows changes in all four areas as well as provides dance and movement therapists with a framework for different client groups such as individuals with depression, Parkinson’s disease, etc. Further research on seniors’ experiences is needed.